Interactions with Powerful Female Colleagues Promote Diversity in Hiring - Battaglini, Marco; Harris, Jorgen M.; Patacchini, Eleonora (Journal of Labor Economics, 2023)
We study the effect of hearing cases alongside female judicial colleagues on the probability that a federal judge hires a female law clerk. Federal judges are assigned to judicial panels at random and have few limitations on their choices of clerks. Using a unique dataset of federal case records merged with judicial hiring information, we find a significant effect of the fraction of copanelists who are female on a male judge’s likelihood of hiring a female clerk. This finding suggests that increases in the diversity of the upper rungs of a profession can create opportunities at the entry level.